How do you find the nth partial sum, determine whether the series converges and find the sum when it exists given #1/(1*3)+1/(3*5)+1/(5*7)+...+1/((2n-1)(2n+1))+...#?

Answer 1

To find the nth partial sum of the series ( \frac{1}{1 \cdot 3} + \frac{1}{3 \cdot 5} + \frac{1}{5 \cdot 7} + \ldots + \frac{1}{(2n-1)(2n+1)} + \ldots ), we first express each term as a fraction and then find a pattern in the series.

The nth term of the series can be written as: [ \frac{1}{(2n-1)(2n+1)} = \frac{1}{4n^2 - 1} ]

Now, let's find the nth partial sum, denoted as ( S_n ): [ S_n = \frac{1}{1 \cdot 3} + \frac{1}{3 \cdot 5} + \frac{1}{5 \cdot 7} + \ldots + \frac{1}{(2n-1)(2n+1)} ]

[ S_n = \frac{1}{4n^2 - 1} + \frac{1}{4(n-1)^2 - 1} + \frac{1}{4(n-2)^2 - 1} + \ldots + \frac{1}{1^2 - 1} ]

Now, let's simplify the terms in ( S_n ) and see if there's a pattern: [ S_n = \frac{1}{4n^2 - 1} + \frac{1}{4n^2 - 9} + \frac{1}{4n^2 - 25} + \ldots + \frac{1}{0} ]

[ S_n = \frac{1}{4n^2 - (2n+1)^2} + \frac{1}{4n^2 - (2n+3)^2} + \frac{1}{4n^2 - (2n+5)^2} + \ldots + \frac{1}{0} ]

We can observe that each term in the series can be written in the form ( \frac{1}{a^2 - b^2} ), which can be decomposed using partial fraction decomposition. However, there isn't a simple arithmetic pattern in the series to directly find a closed-form expression for ( S_n ).

To determine whether the series converges, we can examine the behavior of the nth term as ( n ) approaches infinity. Notice that as ( n ) becomes very large, the terms in the series approach zero. Therefore, by the nth-term test for divergence, since the limit of the nth term as ( n ) approaches infinity is zero, the series converges.

However, finding the exact sum when it exists requires more advanced techniques such as partial fraction decomposition or using other methods like telescoping series.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

The nth partial sunm is #=n/(2n+1)#
The series converge to #1/2#

Let's perform the partial fraction decomposition of the nth term

#1/((2n-1)(2n+1))=A/(2n-1)+B/(2n+1)#
#=(A(2n+1)+B(2n-1))/((2n-1)(2n+1))#

The numerators are the same, we compare the denominators

#1=A(2n+1)+B(2n-1))#
Let #n=1/2#, #=>#, #1=2A#, #=>#, #A=1/2#
Let #n=-1/2#, #=>#, #1=-2B#, #=>#, #B=-1/2#

Therefore,

#1/((2n-1)(2n+1))=(1/2)/(2n-1)-(1/2)/(2n+1)#
#u_n=1/2(1/(2n-1)-1/(2n+1))#

So,

#u_1=1/2(1/1-cancel(1/3))#
#u_2=1/2(cancel(1/3)-cancel(1/5))#
#u_3=1/2(cancel(1/5)-cancel(1/7))#
#u_(n-1)=1/2(cancel(1/(2n-3))-cancel(1/(2n-1)))#
#u_n=1/2(cancel(1/(2n-1))-1/(2n+1))#
#sum_(n=1) ^n=1/2(1-1/(2n+1))=1/2((2n)/(2n+1))#
#=n/(2n+1)#
The nth partial sunm is #=n/(2n+1)#
#lim_(n->+oo)n/(2n+1)=lim_(n->+oo)n/(2n)=1/2#
The series converge to #1/2#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7